Mind Europe's early-stage equity gap - Reinhilde Veugelers (Bruegel, 2011)
Remedying the European Union's deficient overall business research and development performance requires the nurturing of more new companies in new sectors, enabling them to grow to leading-innovator status. This means addressing young leading innovators' access to external finance, particularly early-stage venture capital. The funding system for aspiring young leading innovators ('yollies') needs to be understood as an interconnected system comprising different types of funding at different stages of company lifecycles. Venture capital funds are critical at the early commercialisation stage. Venture capital investors rely on a good deal flow of high-potential investment-ready firms, on skilled investment managers, and on developed exit markets. Poor returns from early-stage investments in Europe on a smaller deal flow have significantly reduced the appetite for early-stage venture capital. This exodus has left a funding gap in Europe for aspiring yollies. The evidence suggests that there are a number of ineffective public schemes supporting mediocre deals at mediocre funds. Shutting those down would free up enough funding to allow a significant shift towards a more effective venture investing system focused on high quality venture capital and innovative projects from aspiring yollies.
Keywords: 330; Risikokapital; Innovationspolitik; EU-Staaten